Utilizing social media technology during the COVID-19 pandemic to assist highly vulnerable populations in the Philippines - Daryn Joy Go; Natalee Hung; Hannah Ferrolino; Kendall Wilson; Mia Choi; Daniel Mayhugh; Lincoln Lau (Health for All Nations, 2020)
National lockdowns and social distancing measures enforced in response to COVID-19 have forced many non-governmental organizations (NGOs) serving in low- and middle-income countries to suspend their operations. While low-income families continue to suffer from hunger and poverty, community quarantine restrictions additionally isolated them from town centers where healthcare, education, food, supplies, and livelihood opportunities are usually accessed. International Care Ministries (ICM) is a Philippine-based NGO that runs a poverty-alleviation program targeted towards extreme low-income households. As we re-evaluated how we may continue to effectively minister and serve our communities despite lockdown measures, we identified two priorities: (1) to serve people's physical needs by providing food and access to healthcare and (2) to serve people's spiritual needs through spiritual nourishment and community. In this field report, we describe how ICM was able to identify and use social network platforms as an alternative to continue both service delivery and spiritual feeding remotely. We hope this example may encourage other development NGOs to persevere as we all continue to seek ways to adapt to these extraordinary and seemingly ever-changing circumstances.